Selective exposure of the fetal lung and skin/amnion (but not gastro-intestinal tract) to LPS elicits acute systemic inflammation in fetal sheep. - Matthew W Kemp; Paranthaman Senthamarai Kannan; Masatoshi Saito; John P Newnham; Tom Cox; Alan H Jobe; Boris W Kramer; Suhas G Kallapur (PLoS ONE, 2013)
Inflammation of the uterine environment (commonly as a result of microbial colonisation of the fetal membranes, amniotic fluid and fetus) is strongly associated with preterm labour and birth. Both preterm birth and fetal inflammation are independently associated with elevated risks of subsequent short- and long-term respiratory, gastro-intestinal and neurological complications. Despite numerous clinical and experimental studies to investigate localised and systemic fetal inflammation following exposure to microbial agonists, there is minimal data to describe which fetal organ(s) drive systemic fetal inflammation. We used lipopolysaccharide (LPS) from E.coli in an instrumented ovine model of fetal inflammation and conducted a series of experiments to assess the systemic pro-inflammatory capacity of the three major fetal surfaces exposed to inflammatory mediators in pregnancy (the lung, gastro-intestinal tract and skin/amnion). Exposure of the fetal lung and fetal skin/amnion (but not gastro-intestinal tract) caused a significant acute systemic inflammatory response characterised by altered leucocytosis, neutrophilia, elevated plasma MCP-1 levels and inflammation of the fetal liver and spleen. These novel findings reveal differential fetal organ responses to pro-inflammatory stimulation and shed light on the pathogenesis of fetal systemic inflammation after exposure to chorioamnionitis.